Clinicopathological Study of Oral Giant Cell Fibroma - Fatimah J.Ismael1 , Bashar H.Abdullah1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Giant Cell Fibroma (GCF) is a relatively rare oral mucosal lesion, so named due to the characteristic giant cells present within the fibrous stroma of the lesion, limited number of clinicopathological studies were performed in previously published literature. This study was performed to evaluate the clinicopathological features of Giant cell fibroma in a sample of Iraqi patients. Formalin-fixed paraffin-embedded sections from 22 giant cell fibroma in period between 2010 and 2018 were retrieved from the laboratory of oral pathology of Baghdad University/College of Dentistry, Clinical data and microscopic features were reviewed and analyzed according to the available surgical reports. The mean age of patients at the time of diagnosis was 29.68 years with slight female predilections (1.4:1), the gingiva is the most common site of occurrence (36.4%), the lesions were 2-10 mm in greatest dimension. The most frequent provisional diagnosis is fibroma (54.5%) and papilloma (27.3%). Histologically, the distinctive diagnostic feature is the presence of mono, bi or multinucleated large stellate giant cells with a mean of 48.59 which is most numerous in the lamina properia beneath the epithelium.